UM ESTUDO SOBRE O PROGRAMA DE EXECUÇÃO DAS ALTERNATIVAS PENAIS PATRONATO IRATI-PR: COM ÊNFASE NO TRABALHO DA ÁREA DE PEDAGOGIA - GONÇALVES, VICTA OGG JONSON (2021)
We present as the object of study the Program of Execution of Criminal Alternatives of the District of Irati-Patronato Irati-PR, created in 2013 and extinct in 2019, which offered legal, pedagogical, psychological and social assistance to graduates of the prison system benefited from the progression to the open regime, parole and / or assisted freedom. Our general objective is: to analyze the implementation, development and extinction of the Program for the Execution of Criminal Alternatives of the District of Irati-PR with emphasis on the work of the Pedagogy area from the perspective of Social Pedagogy. For that purpose, we divided the specific objectives within the three chapters in which this study is structured, being: a) t verify the process of formulating public policies from the perspective of alternative sentences to prison supervised by the Program of Execution of Criminal ternatives-Patronage of the State of Paraná; b) to understand the implementation, development and extinction of the Program for the Execution of Criminal Alternatives of the District of Irati-PR; c) to analyze the legislation that guided the organizational structure of the Program of Execution of Criminal Alternatives of the District of Irati-PR with emphasis on the work of the Pedagogy area; d) to investigate how the process of implementation, development and extinction of the program occurred, seeking understanding about the educational processes that were offered, especially the work developed by the Pedagogy area. In order to analyze this educational public policy, we used the policy cycle approach as a method, in its three contexts: context of influence, context of text production and context of practice. As Mainardes (2018, p.3) explains, in the light of Bowe, Ball and Gold studies (1992) "[...] these contexts are interrelated, do not have a temporal or sequential dimension, and are not linear steps. Each of these contexts presents arenas, places and interest groups and each of them involves disputes and clashes." Thus, the research was forwarded through bibliographic research, documentary and empirical research. However, it is noteworthy that authors were used who focus on the discussion of the perspective of Public Policies, Social Pedagogy, Penal System, Educational System, in order to contextualize our object of analysis. As a technique in the empirical research, an interview was made using a pre-structured script, with five guests, who were appointed in order of interview, being two from the Judiciary system, two from the Patronato and one from State. The structure of this Dissertation occurred in the division by three chapters. Chapter I followed the perspective of the context of influence, with discussions about Public Policies: Guidelines of Social Processes. Chapter II organized the context of the production of the text, and the questions were about the Program for the Execution of Criminal Alternatives of the District of Irati-Patronato Irati-PR with emphasis on the work of the pedagogy area. In Chapter III, the guidelines followed around the presentations of the context of the practice, when the practice of the implementation, development and extinction of the Irati District Patronage Program was contextualized, with emphasis on the work in the Pedagogy area, at this moment the entire proccess of existence of the program was contextualized through the voices of the interviewees. In our analysis of the context of text production, of influence and of practice allowed us to understand how the power struggles happen regarding educational public policies and public policies in general, as well as understanding that the extinction proccess ended up impacting the compliance and surveillance of sentences alternative to prison. We obtained as result of this research considerations about the rethinking of a new institution in the municipality of Irati-PR